Are boat transition states likely to occur in Cope rearrangements? A DFT study of the biogenesis of germacranes - Barquera-Lozada, José Enrique; Cuevas, Gabriel (Beilstein Journal of Organic Chemistry, 2017)
It has been proposed that elemanes are biogenetically formed from germacranes by Cope sigmatropic rearrangements. Normally, this reaction proceeds through a transition state with a chair conformation. However, the transformation of schkuhriolide (germacrane) into elemanschkuhriolide (elemane) may occur through a boat transition state due to the final configuration of the elemanschkuhriolide, but this transition state is questionable due to its high energy. The possible mechanisms of this transformation were studied in the density functional theory frame. The mechanistic differences between the transformation of (Z,E)-germacranes and (E,E)-germacranes were also studied. We found that (Z,E)-germacranolides are significantly more stable than (E,E)-germacranolides and elemanolides. In the specific case of schkuhriolide, even when the boat transition state is not energetically favored, a previous hemiacetalization lowers enough the energetic barrier to allow the formation of a very stable elemanolide that is even more stable than its (Z,E)-germacrane.
Keywords: biogenesis; density functional theory; reaction mechanism; sigmatropic rearrangement; terpenes